2010
DOI: 10.4049/jimmunol.0902182
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Genetic Evidence for a SAP-PKC-θ Interaction Contributing to IL-4 Regulation

Abstract: SAP, an adaptor molecule that recruits Fyn to the SLAM-family of immunomodulatory receptors, is mutated in X-linked lymphoproliferative disease. CD4+ T cells from SAP-deficient mice have defective TCR-induced IL-4 production and impaired T cell-mediated help for germinal center formation; however, the downstream intermediates contributing to these defects remain unclear. We previously found that SAP-deficient CD4+ T cells exhibit decreased PKC-θ recruitment upon TCR stimulation. We demonstrate here using GST-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 66 publications
(113 reference statements)
2
48
0
Order By: Relevance
“…Our data are therefore consistent with CCR7 lo PD-1 hi ICOS hi CD150 lo CD4 T cells being the "GC TFH" cells in RMs (45). Because IL-4 is induced upon CD150/SAP crosstalk and is mediated by FYN and PKC-θ/ NF-κB signaling (13,46), investigating the ratio of CD150 to SAP and the relative function of FYN-and PKC-θ-mediated pathways could inform the mechanisms underlying these polarized cytokine profiles. We found that sorted CCR7 lo PD-1 hi CD4 T cells from chronically infected RMs were capable of providing in vitro help to sorted total or memory autologous B cells, further supporting their definition as TFH cells.…”
Section: Discussionsupporting
confidence: 68%
“…Our data are therefore consistent with CCR7 lo PD-1 hi ICOS hi CD150 lo CD4 T cells being the "GC TFH" cells in RMs (45). Because IL-4 is induced upon CD150/SAP crosstalk and is mediated by FYN and PKC-θ/ NF-κB signaling (13,46), investigating the ratio of CD150 to SAP and the relative function of FYN-and PKC-θ-mediated pathways could inform the mechanisms underlying these polarized cytokine profiles. We found that sorted CCR7 lo PD-1 hi CD4 T cells from chronically infected RMs were capable of providing in vitro help to sorted total or memory autologous B cells, further supporting their definition as TFH cells.…”
Section: Discussionsupporting
confidence: 68%
“…This interaction appears to be important for some, but not all, of the functions of SAP (Cannons et al, 2004(Cannons et al, , 2006Davidson et al, 2004;Nunez-Cruz et al, 2008;Qi et al, 2008). Through R78, SAP can also bind Pak-interacting exchange factor (PIX), the adaptor Nck, and protein kinase C-q (PKC-q) (Cannons et al, 2010;Gu et al, 2006;Li et al, 2009). Unlike SAP, EAT-2 and ERT do not possess the R78-based motif.…”
Section: Introductionmentioning
confidence: 93%
“…Because R78 of SAP can also mediate associations with PIX, Nck, and PKC-q (Cannons et al, 2010;Gu et al, 2006;Li et al, 2009), we ascertained whether Fyn was the critical effector of R78 by performing analogous studies with Fyn-deficient NK cells ( Figure 3A). Fyn-deficient NK cells, as well as Lck-deficient NK cells used as controls, had normal levels of SAP, SLAM family receptors, and CD48 ( Figures 3B and S3A).…”
Section: Fyn Is Required For Activating Function Of Slam Family Recepmentioning
confidence: 99%
“…Such association sequentially mediates Fyn recruitment to the cytoplasmic tail of the CD150 receptor and, following tyrosine phosphorylation, leads to the recruitment of SHIP, docking protein (Dok) 1, and Dok2 (Chan et al, 2003;Chen et al, 2006;Latour et al, 2001;Latour et al, 2003). Therefore, SAP has the ability to simultaneously associate with SLAMF molecules and Fyn, thus forming a trimolecular complex that also reportedly regulates the activation of Vav-1, Casitas B-lineage lymphoma (Cbl), Bcl-10, and protein kinase C-theta (PKC-θ)-mediated activation of NF-κB1 in T cells (Cannons et al, 2004;Cannons et al, 2010b;Claus et al, 2008;Zhong & Veillette, 2008). Furthermore, SAP can additionally engage Lck, which phosphorylates CD84, CD150, CD229 and CD244 (Howie et al, 2002;Martin et al, 2005;Nakajima et al, 2000;Tangye et al, 2003).…”
Section: The Immunoreceptor Tyrosine-based Switch Motif and Cell Signmentioning
confidence: 99%